GEOLOGÍA Y PETROGRAFÍA DEL CERRO BUENAVISTA (CERRO DE LA MUERTE) Y ALREDEDORES, COSTA RICA - Obando Acuña, Luis G. (2011)
The study area, in the Vueltas quadrangle (1:50 000), corresponds to the top hills of CerroBuenavista (Cerro de La Muerte). The outcrops of sedimentary rocks (not differentiated in the map) are shallowwater vulcarenites, medium and coarse breccias, fossiliferous calcarenites and sandy black shales. The intrusions of the Comagmatic Talamanca Group have altered this sequence with important but located hydrothermalalteration. The age of the sequence is possibly Miocene and it can be correlated with the Peña Negra Formation(terrigenous mudstones) and the shallow sequence of dominant sandstones, with Coris Formation.The intrusive rocks, macroscopically and microscopically are described as augite gabbros. The volcanic rockscorrespond with dacites and alkaline basalts (?) belonging to the Aguacate Group, correlationable with GrifoAlto Formation with a Plio-Pleistocene (?) age. This sequence is intruded by andesitic dikes. Dacitic rocks wereobserved cropping out in the Cerro Jaboncillo, forming extrusive domes of Lower Plio-Pleistocene age.The morphological analysis shows three directions of alignments, the dominant one has a NW direction, followedof the less dominant direction NE, and finally the last one is towards the E-W. This suggests that the extrusions probably took advantage of cortical weaknesses to arrive at the surface.